(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Influence of organic manures (10 ton ha-1), nitrogen (50 and 100 kg ha-1), phosphorus (10 and 20 kg ha-1) and potassium (30 and 60 kg ha-1) on the growth and yield of Aloe vera (L.) Burm.f. (Aloe barbadensis Mill.) were evaluated. Experiment was conducted in a randomized design replicated thrice with eleven treatments with NPK and without NPK fertilizers. Highest length of leaf (18 cm), highest leaf area (23.40 cm2plant-1), highest leaf area index 0.06 were observed in ACI10ton ha-1plus N50P10K3O kg ha-1 treatment, highest fresh weight (78.23gplant-1) and highest dry weight (9.58 gplant-1) of plant biomass were observed in GTS 10ton ha-1 treatment. Highest concentration of N (2.69%) and protein content (16.84 %) in the leaf were recorded in GTS10 ton ha-1 treatment. Results revealed that the best growth performance and yield, and protein content in the leaf of Aloe vera was observed in GTS10 ton ha-1 treatment. Dhaka Univ. J. Biol. Sci. 31(2): 203-212, 2022 (July)